SUDUT PANDANG ALIRAN HUMANISTIK TERHADAP MODEL PENDIDIKAN ANDRAGOGI - Bayu, Bayu (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2009)
In-generaltherearetwounderstandthatteachingpedagogythatisvalidand andragogy.Andragogyunderstandis theplacetostudyparticipantsas"adult". Studentsareplacedasthesubjectoftheeducationsystem.Studentsasadults assumedtohave the abilitytoplanwisely,choosematerialsthatareableto analyzeanduseful.Functionasateacherisa  facilitatorandnotdominator. Secondistounderstand  thecurrentdebatethatisstillexperiencingalittle difficult toclassifiedschoolinIndonesiaunderstandwhichofthe  two. This causesdifficultiesclassificationschoolisonlybasedonthenatureofeducation intheschools.SchoolsinIndonesiacanbeclassifiedintoamodernschoorthat isnotdoctrinaire,andbasedonskills